Analysis and Visualization of Seismic Activity Before and After a Major Earthquake for Earthquake Prediction in High-Risk Areas - Calim, Zeynep; Cimen, Sibel; Yildirim, Tulay; Ersoy, Sukru (IEEE, 2025)
In recent years, earthquakes in our country have caused widespread destruction and significant losses. Following these earthquakes, new fault zones have become active, leading to an increase in seismic activity nationwide. Earthquakes generated by active faults are interpreted by seismologists as precursors to major earthquakes. Although the high-risk areas where these earthquakes may occur are known, the exact timing of their occurrence remains unpredictable. Consequently, earthquake analysis and prediction studies have gained prominence in recent years. In this study, two regions where the Golcuk and Duzce earthquakes occurred, located in the western part of the North Anatolian Fault Zone, were examined. Using seismic records from these regions, frequency analyses were conducted for both pre- and post-major earthquake periods. Additionally, earthquake density was visualized through grid-based density estimation. The analysis results indicate findings related to seismic hazard signals and energy transfer.
Keywords: seismic analysis; energy transfer; grid-based density estimation; earthquake density map; frequency analysis; Computer Science; Engineering; Telecommunications